Cystic adrenal lymphangioma: Differential diagnosis - Çobano?lu, Bengü; Karataş, Pervin; Serhatlio?lu, Selami; Do?ru, Osman (Turkiye Klinikleri, 2009)
Adrenal lymphangioma is a very rare entity. It occurs approximately in 0.06% of the general population. Because of lacking characteristic symptoms and signs and clinical insignicance preoperative diagnosis is difficult. Adrenal cysts are usually asymptomatic; if symptoms do occur, they are usually related to the mass effect and include pain, gastrointestinal disturbance, or a palpable mass. Laboratory findings are nonspecific and are usually not helpful as a diagnostic tool. A case of right adrenal cystic lymphangioma in a 68-year-old man was reported. He was admitted to the hospital with abdominal pain and abdominal distention. Ultrasound and computerized tomography (CT) scan showed the mass and suggested a diagnosis of pheochromocytoma or a metastatic mass in the right adrenal gland. The patient underwent surgery and a right adrenalectomy was performed. Histopathological examination and immunohistochemical analysis of the lesion was consistent with a lymphangioma. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Adrenal glands; Vascular neoplasms